The Relationship Of Knowledge, Personal Hygiene, And Stress With The Incidence Of Vaginal Discharge Among Adolescent Female Students At Al-Mujtahiddin Islamic Boarding School, Bogor Regency - Ristia Suningsih; Dewi Kurniati; Rini Kundaryati (Rajaki of Tulip Medika Publisher, 2026)
Abstract Vaginal discharge is fluid released from the vagina other than blood and may be physiological or pathological. Pathological vaginal discharge is an indication of infection and may lead to complications such as pelvic inflammatory disease, infertility, and long-term reproductive health problems. The prevalence of vaginal discharge in Indonesia is approximately 75%, with 31.8% occurring among adolescents aged 15–24 years, 27.6% in West Java Province, and reaching 58.4% in Bogor Regency. This study aimed to analyze the relationship between knowledge, personal hygiene, and stress levels with the incidence of vaginal discharge among adolescent female students at Al-Mujtahiddin Islamic Boarding School, Bogor Regency. This study employed a quantitative analytic method with a cross-sectional design. The sample consisted of 72 adolescent female students who met the inclusion criteria. Data were collected using questionnaires and analyzed using univariate and bivariate analysis with the Chi-Square test. The results showed that 54.2% of respondents experienced physiological vaginal discharge and 45.8% experienced pathological vaginal discharge. Good knowledge was found in 51.4% of respondents, good personal hygiene practices in 41.7%, and low stress levels in 55.6%. There was a significant relationship between knowledge and the incidence of vaginal discharge 0.005, personal hygiene 0.001, and stress level 0.000 with the incidence of vaginal discharge. Knowledge, personal hygiene, and stress levels were significantly associated with the incidence of vaginal discharge among adolescent female students. Therefore, promotive and preventive efforts are needed through improving reproductive health education, encouraging proper personal hygiene behavior, and stress management among adolescent female students to prevent vaginal discharge.